Development of a Storm Surge Prediction Model - Rivera, Paul; Delas Alas, Jorge (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 1 (1992), 2007)
A numerical model based on the depth-integrated hydrodynamical equations is formulated. It is used to study the response of an ideal ocean shelf region of limited areal extent subjected to the passage of hypothetical cyclones (symmetric and asymmetric) with known characteristics. Four sets of numerical experiments are conducted to investigate storm surges generated within the model basin. The first set considers the effect of varying cyclone directions of approach relative to the basin on the resulting storm surge. The second set considers the effect of varying cyclone speeds and sizes, the third on the effect of varying shelf widths, and the fourth on the effect of asymmetry in the cyclone wind field. Results for the seven cyclone directions investigated showed potential surge threats for cyclones that made landfall to the right or center of the model basin. The highest magnitude of surges was generated by a cyclone which crossed the basin and made landfall at the center of the coastline. The effect of the cyclone speed did not matter much in the peak surge generated, whereas the effect of the cyclone size was significant. Furthermore, the effect of varying shelf widths clearly demonstrated the reduced effect of the surface stress in deeper waters. Lastly, the asymmetry of the cyclone wind field has a substantial effect on the magnitudes of surges generated.